2019
DOI: 10.1029/2018tc005445
|View full text |Cite
|
Sign up to set email alerts
|

Pangea and the Lower Mantle

Abstract: We show that the peripheral Pangea subduction zone closely followed a polar great circle. We relate it to the band of faster-than-average velocities in lowermost mantle. Both structures have an axis of symmetry in the equatorial plane. Assuming geologically long-term stationarity of the deep mantle structure, we propose to use the axis of symmetry of Pangea to define an absolute reference frame. This reference frame is close to the slab remnants and NNR frames of reference but disagrees with hot spot-based fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 79 publications
(183 reference statements)
2
31
0
Order By: Relevance
“…Two large regions of low S wave speeds, LLSVPs, one beneath the Pacific and the other beneath Africa, dominate the structure of the lower mantle (Figures 2, 3, 5, and 6). As discussed above, during much of Mesozoic time Pangea seems to have overlain the LLSVP beneath Africa (Chase & Sprowl, 1983;Le Pichon et al, 2019;Le Pichon & Huchon, 1983, which suggests that the LLSVPs are long lived features, an inference that Busse (1983) associated with the low order of the convective planform, and as many have subsequently argued (e.g., Ballmer et al, 2017;Deschamps et al, 2011;Gonnermann et al, 2002;Heyn et al, 2018;Trønnes et al, 2019). Dziewonski et al (2010) suggested that these features might be fixed in place by their ensuring that one of the principal components of the moment of inertia tensor lies along the equator.…”
Section: Surface Manifestations Of Convective Flow In the Lower Mantlementioning
confidence: 96%
See 3 more Smart Citations
“…Two large regions of low S wave speeds, LLSVPs, one beneath the Pacific and the other beneath Africa, dominate the structure of the lower mantle (Figures 2, 3, 5, and 6). As discussed above, during much of Mesozoic time Pangea seems to have overlain the LLSVP beneath Africa (Chase & Sprowl, 1983;Le Pichon et al, 2019;Le Pichon & Huchon, 1983, which suggests that the LLSVPs are long lived features, an inference that Busse (1983) associated with the low order of the convective planform, and as many have subsequently argued (e.g., Ballmer et al, 2017;Deschamps et al, 2011;Gonnermann et al, 2002;Heyn et al, 2018;Trønnes et al, 2019). Dziewonski et al (2010) suggested that these features might be fixed in place by their ensuring that one of the principal components of the moment of inertia tensor lies along the equator.…”
Section: Surface Manifestations Of Convective Flow In the Lower Mantlementioning
confidence: 96%
“…Some pointed out that hot spots seemed to preferentially overlie the regions of low speeds and geoid highs, especially after masses of subducting slabs of lithosphere were taken into account (e.g., Anderson, ; Cazenave et al, ; Chase, , Crough & Jurdy, ). Chase and Sprowl () and Le Pichon and Huchon (, ); Le Pichon et al, ] reconstructed continents to their relative positions at ~125 Ma (though with little difference among reconstructions between 100 and 200 Ma); to determine past longitudes, they either assumed hot spots to be approximately fixed or they kept Africa essentially in its past position. In such reconstructions, Pangea occupied one hemisphere centered on one of the regions of large geoid highs in the Degree‐2 pattern.…”
Section: Whole‐mantle Convection and The Lower Mantlementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 and Lenardic et al, 2011;Robin et al, 2007;Thayalan et al, 2006). Plate reconstructions and geological data suggest that subduction zones probably encircled Rodinia and to a lesser extent Pangea by the time these supercontinents were each formed (e.g., East et al, 2019;Evans, 2009;Lee et al, 2013;Le Pichon et al, 2019;Li et al, 2013;Müller et al, 2016). Depending on the continuity, geometry, and age of subducting slabs, such a planform can have varied consequences for the character and extent of mantle thermal mixing.…”
Section: The Mantle Response To the Assembly And Breakup Of Supercontmentioning
confidence: 99%